1990
DOI: 10.1364/josab.7.001481
|View full text |Cite
|
Sign up to set email alerts
|

Optical measurements of charge-carrier mobilities in photorefractive sillenite crystals

Abstract: Analyses of the kinetics and magnitude of enhanced two-wave mixing gain under externally applied square-wave and sinusoidal electric fields are used to determine photocarrier drift mobility. These direct measurements do not require that any other photorefractive parameters be known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1990
1990
1998
1998

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 8 publications
(6 reference statements)
0
5
0
2
Order By: Relevance
“…This analysis leads to an important result. The diffusion length measured by decay-time analysis of a photorefractive grating under uniform cw illumination2151622 or obtained by separately measuring the apparent mobility and recombination time in two-wave mixing with an ac field 24 is the same as that measured in picosecond experiments. Indeed, L (kBT TAR 2 /e) 1 2 = (kBTjT_/e)11 2 .…”
Section: Comparison With Measurements In the Continuous Regimementioning
confidence: 95%
“…This analysis leads to an important result. The diffusion length measured by decay-time analysis of a photorefractive grating under uniform cw illumination2151622 or obtained by separately measuring the apparent mobility and recombination time in two-wave mixing with an ac field 24 is the same as that measured in picosecond experiments. Indeed, L (kBT TAR 2 /e) 1 2 = (kBTjT_/e)11 2 .…”
Section: Comparison With Measurements In the Continuous Regimementioning
confidence: 95%
“…Le champ £, comporte une composante rapide qui oscille à une fréquence \jz E directement liée à la mobilité des charges [59,60]. Cette oscillation s'amortit avec une constante de temps de f. L'existence de deux constantes de temps provient de ce que le champ de charge d'espace E l résulte de la superposition d'un champ provenant de la modulation spatiale dans les centres profonds E'°n et d'un champ dû à la modulation spatiale des porteurs de charge E\ c : ||A/fi=-r + /r_||«l .…”
Section: Régime Transitoireunclassified
“…La même explication physique rend compte des résonances en fonction de la fréquence que l'on peut observer sous champ alternatif sinusoïdal à plus haute fréquence [59,62,63]. On peut grossièrement les expliquer de la façon suivante.…”
Section: Résonances Sous Champ éLectrique Sinusoïdalunclassified
“…In a more detailed theory [104,31], it was shown that an oscillating (both imaginary and real) space-charge field arises in addition to the static space-charge field. Moreover, in [105] it was experimentally shown using the alternating field technique that there exist high-frequency resonances of the gain factor ( ) (on the scale of ten kilohertz) in BGO. They were attributed to the high-frequency branch of space-charge waves (this branch will be discussed at the end of the paper).…”
Section: The Methods Of Alternating Applied Fieldmentioning
confidence: 99%